Predictors and interdependence of family support in a random sample of long‐term young breast cancer survivors and their biological relatives. (5th September 2018) - Katapodi, Maria C.; Ellis, Katrina R.; Schmidt, Franziska; Nikolaidis, Christos; Northouse, Laurel L.
Abstract: Objective: Women diagnosed with breast cancer younger than 45 years (young breast cancer survivors—YBCS) and their biological relatives face significant stressors. Although family support is an important coping resource, little is known about YBCS' and relatives' support and whether it is interdependent. The study described family support in YBCS and their biological relatives; identified demographic, clinical, and psychosocial predictors of support; and determined the interdependence of support in YBCS‐relatives family units. Methods: Data were collected from a random sample of YBCS and their first‐ or second‐degree female relatives. Actor‐partner interdependence models (APIM) explored predictors and interdependence of YBCS' and relatives' family support in dyads (YBCS and relative) and triads (YBCS and two relatives). Results: Among n = 310 YBCS and n = 431 first‐ or second‐degree relatives, family support was higher in triads compared to dyads. APIMs identified actor effects in dyads, and actor and partner effects in triads. Across all family units, YBCS' higher self‐efficacy was associated with higher YBCS support ( actor effect ) and relative support ( partner effect ); YBCS' prior diagnosis of depression was associated with lower YBCS and relative support ( actor and partner effect ); cost‐related lack of access to care was associated with lower support among YBCS ( actor effect ) and relatives ( actor and partner effect ). Conclusions: Family support was interdependent and was affected by self‐efficacy, depression, and access to care. Interventions should include YBCS and relatives, enhance self‐efficacy and access to care. Abstract : Women diagnosed with breast cancer younger than 45 years old (young breast cancer survivors—YBCS) and their biological relatives face significant stressors. Data were collected from a random sample of YBCS, stratified by race, and their first‐ or second‐degree female relatives. Actor‐partner interdependence models explored predictors and interdependence of YBCS' and relatives' family support in dyads (YBCS‐one relative) and triads (YBCS‐two relatives). YBCS' and relatives' family support is interdependent.